A Study on the Selection of Milling Cutter Material for HARDOX 500 Steel Based on Wear Using Taguchi, Entropy, and PIV Methods - Tam, Dang Thanh; Ky, Le Hong; The, Than Van; Dat, Huynh Tan (Engineering, Technology & Applied Science Research, 2026)
This study investigates the selection of hard alloy insert coating materials for milling HARDOX 500 steel based on wear behavior, using a combination of Taguchi design, Entropy weighting, and the PIV multi-criteria decision-making method. Experiments were conducted on a HAAS CNC milling machine using specialized measurement equipment. The results identify the APMT1604PDER-LH insert coated with KG7016 as the most suitable option. Under the machining conditions of cutting speed v = 100 m/min and feed rate f = 0.25 mm/tooth, the KG7016-coated insert exhibited the largest flank wear (VBmax) and wear rate by mass (VM), while simultaneously achieving the lowest Surface Roughness (SR), which is symbolized with Ra. Rather than assigning equal importance to all performance criteria, the Entropy method was employed to objectively determine their relative weights, yielding values of 0.0571 for Ra, 0.4646 for VBmax, and 0.4782 for VM. These findings provide a basis for improving the service life of hard alloy cutting inserts in HARDOX 500 steel milling, particularly through the application of heating-assisted machining techniques.